META ANALISIS PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN MATEMATIS SISWA - Desy Carolina Sihombing; Nora Susilowaty (Universitas Bhinneka PGRI, 2023)
Project based learning is a type of learning that will be researched to measure the effect on students’ mathematical abilities. Every project-based learning analysis on mathematical skills may allow distinct effects for every aspect, whether mathematical skills components, different educational level, and teaching materials. Studies related to project-based learning researched and developed more and more, with the result that require reassessment from previous researches to conclude the accurate result. The goal of this research is to represent the effect of project-based model learning on the students’ mathematical ability altogether, each mathematical skills element, educational level component, and teaching materials component. The population of this study is researches regarding the effect of project-based learning model on students’ mathematical abilities published between 2015 to 2022. By data coding, 22 studies have been earned that fulfil the indicator. The data analysis technique uses a large effect size analysis. The outcome of this study is that the influence project based learning model on mathematical ability altogether has an exceptional effect with the effect size value of 1,32, the effect on mathematical ability aspect has an exceptional effect on comprehension mathematical ability with the effect size value of 2,05, the effect on educational level element has an exceptional effect on the college level with effect size value of 1,52, and the effect on teaching materials has an exceptional effect on algebraic material with effect size value of 3,93.